Genetics of acheiropodia (“the handless and footless families of Brazil”): VIII. Penetrance and expressivity - Freire‐Maia, Ademar (Wiley, 1975)
The acheiropodia data are shown to be consistent with the hypothesis of a fully penetrant gene in the homozygous state. The expressivity is shown to be generally constant, with some minor variation between individuals as well as between the two sides of the same affected person. Copyright © 1975, Wiley Blackwell. All rights reserved